Experimental study on consolidation characteristics of deep clayey soil in a typical subsidence area of the North China Plain - Liu, Fengjunnan; Qi, Jianfeng; Guo, Haipeng; Wang, Yunlong; Guo, Kaijie; Zang, Xisheng (Frontiers in Environmental Science, 2022)
Land subsidence is an important environmental problem in the North China Plain (NCP). A typical subsidence area mainly located on adjoining areas of Beijing and Hebei provinces was selected to study the consolidation characteristics of deep clayey soil. Clay samples were collected from 14 boreholes at different depths, and the compression and consolidation behavior of the soil was analyzed by high-pressure oedometer tests. Results show that the deformation amount and deformation stabilization time in the primary consolidation stage increase with the load but decrease with the sampling depth. The nonlinear compression model of e-log(p) does not fit well for deep normally-consolidated clayey soil, the log(e+ec)–logp model fit the shallow clayey soil better than the deep clayey soil, and the hyperbolic model fits almost all soil samples well. Based on statistical theory, the soil consolidation equation CE_NCP was established for calculating the relationship between the degree of consolidation and the time factor in subsidence areas. The equations were fitted with the data obtained from high-pressure consolidation tests to obtain three parameters a, b and c, which are applied to the consolidation calculations for soil samples at depths of 0-100 m, 100-200 m, 200-300 m and 300-400 m, respectively. The applicability of CE_NCP equation was evaluated by comparing it to the analytical solution of Terzaghi’s consolidation equation, results showing that CE_NCP equation is more suitable for the calculation of the consolidation in the study area than the Terzaghi’s analytical solution. Eventually, the CE_NCP equation was successfully used to estimate the degree of consolidation in a subsidence area of Lang Fang City in the NCP.